The importance of aboveground–belowground interactions on the evolution and maintenance of variation in plant defense traits - van Geem, Moniek; Gols, Rieta; van Dam, Nicole M.; van der Putten, Wim H.; Fortuna, Taiadjana; Harvey, Jeffrey A. (Frontiers in Plant Science, 2013)
Over the past two decades a growing body of empirical research has shown that many ecological processes are mediated by a complex array of indirect interactions occurring between rhizosphere-inhabiting organisms and those found on aboveground plant parts. Aboveground–belowground studies have thus far focused on elucidating processes and underlying mechanisms that mediate the behavior and performance of invertebrates in opposite ecosystem compartments. Less is known about genetic variation in plant traits such as defense as that may be driven by above- and belowground trophic interactions. For instance, although our understanding of genetic variation in aboveground plant traits and its effects on community-level interactions is well developed, little is known about the importance of aboveground–belowground interactions in driving this variation. Plant traits may have evolved in response to selection pressures from above- and below-ground interactions from antagonists and mutualists. Here, we discuss gaps in our understanding of genetic variation in plant-related traits as they relate to aboveground and belowground multitrophic interactions. When metabolic resources are limiting, multiple attacks by antagonists in both domains may lead to trade-offs. In nature, these trade-offs may critically depend upon their effects on plant fitness. Natural enemies of herbivores may also influence selection for different traits via top–down control. At larger scales these interactions may generate evolutionary “hotspots” where the expression of various plant traits is the result of strong reciprocal selection via direct and indirect interactions. The role of abiotic factors in driving genetic variation in plant traits is also discussed.